ISLAMIC COUNSELING INTERVENTIONS FOR ADDRESSING LGBT BEHAVIOR IN ACCORDANCE WITH INDONESIAN LEGAL PROVISIONS - Tresna Suhartoni; Dody Riswanto; Syifa Jauhar Nafisah (Al-Tazkiah Jurnal Bimbingan dan Konseling Islam, 2024)
This study investigates the application of Islamic counseling interventions to address LGBT behavior among students in schools, with a focus on mental and spiritual guidance grounded in Indonesian legal provisions, specifically Article 292 of the Criminal Code and Article 414, paragraph (1) of Law No. 1/2023. Employing a qualitative research design, the study engaged 24 participants, utilizing data collection techniques such as interviews, observations, document analysis, and audio-visual materials. Data analysis was conducted through triangulation, synthesis, interpretation, and the formulation of propositions. The findings reveal that Islamic counseling effectively mitigates LGBT behaviors among students through spiritual practices, including daily prayers, Quran recitation, memorization of short surahs, and transcription of Quranic verses. From a legal perspective, LGBT-related actions are in violation of Article 292 of the Criminal Code and Article 414, paragraph (1) of Law No. 1/2023, which stipulate criminal penalties ranging from 5 to 9 years of imprisonment. The imposition of these legal sanctions serves as a deterrent, encouraging students to critically reflect on the potential consequences of their actions. This research contributes a novel approach by integrating a humanistic and religious framework within counseling interventions, while also emphasizing the role of Indonesian legal regulations in fostering legal awareness and deterring unlawful behavior. This dual approach highlights the potential of combining spiritual guidance with legal education to address behavioral challenges among students.